Ok so first we have to solve for x
The value of x is already given in the equation x = y - 5
Than we plug in the value of x into the second equation so that only one variable is present to find the numerical value of y. (By the way y - 5 = -5 + y, I just reordered the equation to make it easier for me)
11(y - 5) - y = -25
11y - 55 - y = -25
10y - 55 = -25
10y = +30 (here I added +55 to both sides to isolate the variable)
y = 3(here I divided each side by 10 to truly isolate the variable and to find the value of y)
Now we plug in y = 3 into the first equation
x = y - 5
x = 3 - 5
x = -2
Therefore, x = -2 and y = 3
Hope this helps!